Hyperons and massive neutron stars: the role of hyperon potentials - Weißenborn-Bresch, Simon Alexander; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Nuclear physics. A, Nuclear and hadronic physics, 2012)
The constituents of cold dense matter are still far from being understood. However, neutron star observations such as the recently observed pulsar PSR J1614-2230 with a mass of 1.97±0.04M⊙ help to considerably constrain the hadronic equation of state (EoS). We systematically investigate the influence of the hyperon potentials on the stiffness of the EoS. We find that they have but little influence on the maximum mass compared to the inclusion of an additional vector-meson mediating repulsive interaction amongst hyperons. The new mass limit can only be reached with this additional meson regardless of the hyperon potentials. Further, we investigate the impact of the nuclear compression modulus and the effective mass of the nucleon at saturation density on the high density regime of the EoS. We show that the maximum mass of purely nucleonic stars is very sensitive to the effective nucleon mass but only very little to the compression modulus.
Gesehen am 09.05.2019